Development and usability testing of a depth camera–based web application for functionally relevant foot kinematics analysis - Anestherita, Fitri; Tulaar, Angela B. M.; Rachmawati, Maria Regina; Yunir, Em; Harbuwono, Dante Saksono; Werdhani, Retno Asti; Safri, Ahmad Yanuar; Rachmadi, Muhammad Febrian; Nadhif, Muhammad Hanif; Hawalie M, Azwien Niezam; Nugraha, Boya; Putri, Safa Nabila; et al. (Frontiers in Medical Technology, 2025)
IntroductionKineFeet, a depth camera-based web tool for analyzing functional foot kinematics, was developed and tested in this study. The program was optimized for usability, affordability, and clinical relevance through an iterative design and development process.MethodsThe Azure Kinect DK camera records and analyzes sagittal and frontal plane foot movements in real time. A usability-focused study was created. Five physiatrists tested the KineFeet prototype for its ability to assess foot kinematics. Performance was measured by task completion success, error rate, and time. The System Usability Scale (SUS) measured user satisfaction. Quality assessments were also obtained through semi-structured interviews.ResultsParticipants achieved an average success rate of 96.29%, with an error rate of 0.074% and an average completion time of 10 min 11 s. Time-Based Efficiency (TBE) showed that user performance (0.0442 tasks/s) was 1.21 times slower than expert user performance (0.05348 tasks/s). SUS yielded an average score of 66.5, indicating a good level of satisfaction and user acceptance.ConclusionKineFeet represents a promising innovation in assessing functional foot kinematics. The system demonstrated strong usability in preliminary testing and holds potential for broader clinical adoption following further development.